Challenges of Imprisonment in the Nigerian Penal System: The Way Forward - Shajobi-Ibikunle, Gloria D (American Journal of Humanities and Social Sciences, 2014)
This paper traces the customary methods of dealing with offenders prior to colonial rule in Nigeria to the current state of facilities and operations in Nigerian prisons. It critically analyses the condition of the incarcerated offender, the measures put in place for their rehabilitation vis a vis the united nations standard minimum rules for the treatment of offenders. It finds that the prisons are overcrowded, conditions are deplorable with inadequate rehabilitation and aftercare provisions. This paper recommends greater use of fines by courts; restitution, mediation, probation and community service as non-custodial measures for minor and non-violent offenders. Several measures are recommended for rehabilitation and aftercare of convicts.